Plastic closure of bone defects of anterior cranial fossa floor in surgery of benign and malignant craniofacial tumors - Orest I. Palamar; Andriy P. Huk; Dmytro I. Okonskyi; Dmytro S. Teslenko; Ruslan V. Aksyonov; Nazarii V. Lazko (Ukrainian Neurosurgical Journal, 2022)
Objective: to analyze the results of using various methods of plastic closure of bone defects of the anterior cranial fossa (ACF) floor when removing craniofacial tumors of the ACF floor depending on the size of the defect. Materials and methods. A retrospective analysis of treatment outcomes of 122 patients with craniofacial tumors of the ACF floor was carried out. According to the nature of the lesions malignant craniofacial tumors were detected in 98 (80.3%) patients, and benign ones in 24 (19.7%) patients. The following neurosurgical approaches to craniofacial tumors of the ACF floor were used: bifrontal - in 58 (47.5%) patients, subcranial - in 49 (40.2%), transbasal Derome - in 8 (6.5%), frontotemporal - in 4 (3.25%), expanded endoscopic - in 3 (2.45%). In 52 (42.6%) cases, endoscopic endonasal assistance was used, most often in the case of plasty of large ACF floor defects to revise the surgical defect, assess the sufficiency of plasty and tamponade of the nasal cavity with balloon catheters. Results. Patients were divided into groups depending on the bone defect of the ACF floor: median - in 27 (22.1%), middle-expanded - in 71 (58.2%), middle-lateral - in 24 (19.7%). The following types of plasty of the bone defect of the ACF floor were used: pedicle flap - 83 (68.0%) cases, free flap - 22 (18.1%), pedicled periosteal flap with reinforcement - 17 (13.9%). Postoperative complications occurred in 17 (13.9%) patients: nasal liquorrhea in 10 (8.2%) patients (of which 6 underwent reoperation to eliminate it), in 7 patients it was complicated by meningoencephalitis, in other 7 (5.7 %) - meningoencephalitis without signs of nasal cerebrospinal fluid. Postoperative mortality was 0.71% (1 patient). The frequency of nasal cerebrospinal fluid in the group of plasty using a free flap was 13.6% (3 cases), meningoencephalitis - 4.5% (1 observation), in the group of plasty using pedicle flap - 4.8% (4 cases) and 6.0% (5 observations), in the group of plasty using a pedicle flap with reinforcement - 17.6% (3 cases) and 11.7% (2 observations). In 33 (27.1%) cases the use of the author's method of bone defect plasty of the ACF floor with duplication of complications were not registered. Conclusions. Significant size and spread of bone defects of the ACF floor increase the risk of postoperative complications. The use of free flaps for plasty of the bone defect of the ACF floor is ineffective and is associated with a high risk of complications. The proposed method of plasty of the posterior parts of the ACF floor by duplication of the periosteal flap promotes the sealing of the posterior parts, where suturing causes certain difficulties. Reinforcement of plasty from the side of the nasal cavity due to endoscopic technique using tamponade or balloon catheters reduces the incidence of postoperative complications.